Implementación de un ERP para mejorar el proceso de venta y facturación en empresa de vehículos eléctricos personales - Mc Farlane Olazabal, Javier Arturo (2022)
INMOTION INMOTION GROUP SRL, commercially known as Inmotion Peru, is a Peruvian company established in 2018 for the import, distribution and sale of electric vehicles for personal mobility, which has a direct relationship and exclusive agreement with the manufacturer Inmotion Technologies based in Shenzhen, China. The electric vehicles that are marketed are the following: unicycles, scooters, bicycles and bicycles. With the aim of improving people's quality of life; and helping to reduce the environmental impact and the carbon footprint, Inmotion Peru offers an alternative solution for daily transportation. Therefore, it offers constant support, from the first contact, purchase decision, use of the product and after-sales service. In addition, Inmotion is characterized by having a close relationship with each client, identifying the product that meets their needs. In the case of the bicycle, the use is like a conventional one, but with levels of assistance for which the difficulty is similar; the scooter requires a light balance and is operated with accelerator and brake, like the previous equipment the balance is similar to that of a non-electric one; The bike can be used with a stand up to chest height to give it greater stability or with a smaller stand to maneuver it with the legs (knees specifically); finally, the unicycle requires an average learning time of thirty To know the preference of consumers and their needs, we based on the average minutes since it is a new skill that must be acquired. In this last team, the company has focused on constant support to give users security and confidence. To know the preference of consumers and their needs, we based on the average distances, travel time and daily budget, from the study carried out by the Graduate School of the Universidad del Pacífico and the consulting firm Marketwin. The objective of Inmotion is to improve the quality of people’s life, therefore, it is always in constant search of clients who are encouraged by a change in their transport routine; However, there has been a problem with the sales and billing process where the time used is high and focus is lost on other activities of the company, such as finding clients, improving its own website or social networks, negotiation with suppliers, among others. For this reason, the proposed solution is the implementation of an ERP that performs the entire sales process, invoicing, synchronization with SUNAT and sending proof of payment automatically. For this alternative solution, both scenarios and the annual cost that this implementation would generate versus the man-hour used were considered.